Navigating the double bind: Transformations to balance contextual responsiveness and authenticity in women's leadership development - Gelaye Debebe (Cogent Business & Management, 2017)
Women leaders' double bind arises from followers' contradictory expectations that are rooted in the societal female gender role and the organizational leader role. Using qualitative data from alumnae of the Women's Leadership Series (WLS) of the Consultative Group for International Agricultural Research, this paper examines whether and how formal training enables women to more effectively navigate this double bind. Findings show that the WLS fostered four types of leadership transformations: hidden to visible leadership, inflexible to receptive leadership, attenuated to expanded leadership, and discouraged to inspired leadership. Interpreting these transformations through the lens of three ideas from the leadership effectiveness literature—context, authenticity, and behavior—this paper proposes a grounded theory, dual contingency model of leadership effectiveness for women. The model suggests that effective leadership behavior accounts for the demands of context and authenticity and identifies four unique pathways through which inattention to either contingency arises and how imbalance is identified and balance is restored. By elucidating these four pathways, the model enriches the literature on leadership effectiveness and provides insights into how women may successfully navigate the double bind.
Keywords: 650